Group versus Individual Lending in Microfinance - Maria Lehner (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
Microfinance is typically associated with joint liability of group members. However, a large part of microfinance institutions rather offers individual instead of group loans. We analyze the incentive mechanisms in both individual and group contracts. Moreover, we show that microfinance institutions offer group loans when the loan size is rather large, refinancing costs are high, and competition between microfinance institutions is low. Otherwise, individual loans are offered. Interestingly, our analysis predicts that individual lending in microfinance will gain in importance in the future if microfinance institutions continue to get better access to capital markets and if competition further rises.
urn:nbn:de:bvb:19-epub-7486-4
Keywords: F37; G21; G34; L13; O16; 330; Mikrofinanzierung; Kreditgeschäft; Genossenschaftsbank; Theorie